2011
DOI: 10.1182/blood-2010-01-261123
|View full text |Cite
|
Sign up to set email alerts
|

Silent cerebral infarcts occur despite regular blood transfusion therapy after first strokes in children with sickle cell disease

Abstract: Children with sickle cell disease (SCD) and strokes receive blood transfusion therapy for secondary stroke prevention; despite this, approximately 20% experience second overt strokes. Given this rate of second overt strokes and the clinical significance of silent cerebral infarcts, we tested the hypothesis that silent cerebral infarcts occur among children with SCD being transfused for secondary stroke prevention. A prospective cohort enrolled children with SCD and overt strokes at 7 academic centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
230
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(237 citation statements)
references
References 18 publications
5
230
2
Order By: Relevance
“…Even with blood transfusion therapy, children with SCA and overt strokes still have a rate of infarct recurrence as high as 22% over a median of 10 years (overt stroke only) [78], or even 45% over 5.5 years (when both silent infarcts and overt stroke are included) [79]. Further after the first stroke while receiving blood transfusion therapy, 35% had a third stroke while receiving blood transfusion therapy with hemoglobin S levels as low as 1%, 9%, 22%, 25%, 26%, and 55% at the time of the second or third stroke [78,79].…”
Section: Stroke Prevention In Scamentioning
confidence: 99%
See 1 more Smart Citation
“…Even with blood transfusion therapy, children with SCA and overt strokes still have a rate of infarct recurrence as high as 22% over a median of 10 years (overt stroke only) [78], or even 45% over 5.5 years (when both silent infarcts and overt stroke are included) [79]. Further after the first stroke while receiving blood transfusion therapy, 35% had a third stroke while receiving blood transfusion therapy with hemoglobin S levels as low as 1%, 9%, 22%, 25%, 26%, and 55% at the time of the second or third stroke [78,79].…”
Section: Stroke Prevention In Scamentioning
confidence: 99%
“…Further after the first stroke while receiving blood transfusion therapy, 35% had a third stroke while receiving blood transfusion therapy with hemoglobin S levels as low as 1%, 9%, 22%, 25%, 26%, and 55% at the time of the second or third stroke [78,79]. Based on the high rate of infarct recurrence even with rigorous blood transfsuion therapy, HLA-matched sibling hematopoietic stem cell transplantation is now considered the optimal therapeutic option for children with overt strokes.…”
Section: Stroke Prevention In Scamentioning
confidence: 99%
“…HU did not prevent secondary stroke in children with SCD when transfusions therapy was switched to HU. A prospective multicentre [27] suggested that new silent cerebral infarction can develop in transfused children with a history of overt stroke. This high incidence of silent cerebral infarction in transfused patients was similar to our observations in HbS-ß thalassemia.…”
Section: E262mentioning
confidence: 99%
“…18 A more recent report revealed that children with SCD who had overt strokes and were receiving regular blood transfusion continue to experience a high rate of silent cerebral infarcts. 28 The role of transfusion therapy in preventing silent infarcts in children with normal TCD velocities has been questioned. 2 Our study reveals that at least in patients with abnormal TCD velocities who revert to normal with transfusions, discontinuation from the transfusion program will increase the risk of silent infarction.…”
Section: Discussionmentioning
confidence: 99%
“…27 The benefit of transfusion in the prevention of silent cerebral infarction in children with SCD seems to depend on the patient's cerebrovascular status. 28 Analysis of the STOP trial revealed that transfusion therapy lowers the risk Figure 1. Brain MRI findings in the study population at study entry and study end.…”
Section: Discussionmentioning
confidence: 99%